Database system concepts - Silberschatz, Abraham; Korth, Henry F.; Sudarshan, S. (New York, NY ; India : McGraw-Hil Education (India) Private Ltd., 2018)
Presents the fundamental concepts of database management. This text is suitable for a first course in databases at the junior/senior undergraduate level or the first year graduate level.
Chapter 1: IntroductionPart 1: Relational DatabasesChapter 2: Introduction to the Relational ModelChapter 3: Introduction to SQLChapter 4: Intermediate SQLChapter 5: Advanced SQLChapter 6: Formal Relational Query LanguagesPart II: Database DesignChapter 7: Database Design and the E-R ModelChapter 8: Relational Database DesignChapter 9: Application Design and DevelopmentPart III: Data Storage and QueryingChapter 10: Storage and File StructureChapter 11: Indexing and HashingChapter 12: Query ProcessingChapter 13: Query OptimizationPart IV: Transaction ManagementChapter 14: TransactionsChapter 15: Concurrency ControlChapter 16: Recovery SystemPart V: System ArchitectureChapter 17: Database-System ArchitecturesChapter 18: Parallel DatabasesChapter 19: Distributed DatabasesPart VI: Data Mining and Information RetrievalChapter 20: Data MiningChapter 21: Information RetrievalPart VII: Specialty DatabasesChapter 22: Object-Based DatabasesChapter 23: XMLChapter 24: Advanced Application DevelopmentChapter 25: Advanced Data Types and New ApplicationsChapter 26: Advanced Transaction ProcessingPart IX: Case StudiesChapter 27: PostgreSQLChapter 28: OracleChapter 29: IBM DB2 Universal DatabaseChapter 30: Microsoft SQL ServerPart X: AppendicesAppendix A: Detailed University SchemaAppendix B: Other Relational Query LanguagesAppendix C: Advanced Relational Database DesignAppendix D: Network ModelAppendix E: Hierarchical Model
Includes bibliographical references( pages 1283-1314 ) and index.
CSE
Keywords: Database management; Computer science